2017
DOI: 10.1016/j.ijid.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

New tuberculosis drug leads from naturally occurring compounds

Abstract: Tuberculosis (TB) continues to be a significant cause of mortality and morbidity worldwide. An estimated 2 billion individuals are infected with Mycobacterium tuberculosis and annually there are approximately 10 million new cases of clinical TB and 1.5 million deaths. Currently available drugs and vaccines have had no significant impact on TB control. In addition, the emergence of drug resistant TB is considered a public health crisis, with some strains now resistant to all available drugs. Unfortunately, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 113 publications
1
55
0
2
Order By: Relevance
“…Tuberculosis (TB) affects two billion individuals, with ten million new cases and 1.5 million deaths reported each year (Quan et al, 2017). Multidrug-resistant, extensively drugresistant and totally drug-resistant strains of tuberculosis complicate the already tedious treatment protocol (Balganesh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis (TB) affects two billion individuals, with ten million new cases and 1.5 million deaths reported each year (Quan et al, 2017). Multidrug-resistant, extensively drugresistant and totally drug-resistant strains of tuberculosis complicate the already tedious treatment protocol (Balganesh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are extremely useful templates for the development of a number of the new drug molecules and they have received immense attention as potential anti‐TB agents . Various natural products have been reported to show resistant against strains of Mycobacterium tuberculosis . No new anti‐TB drugs have been developed in the TB therapy in the course of the past few years, creating an urgent need of design and developing of new drugs and strategies for an effective TB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the potential of natural extracts as the basis for new drugs [6,7]. Microorganisms and plants have exceptional chemical and structural diversity and represent a valuable source of biologically active molecules with potential as new antimicrobials [8].…”
Section: Introductionmentioning
confidence: 99%